Metode Konseling dalam Membantu Mengurangi Kencanduan Rokok pada Karyawan Politeknik Kesehatan Kemenkes Pangkalpinang. - Syamsul Rizal Sinulingga (Politeknik Kesehatan Tanjung Karang, 2018)
Indonesia is the country with the third largest number of smokers around the world about 65 Milion people. This count will be increased if the government not make rules for the smoker and tobacco industries and do not application avoid of advertisement of tobacco. Until now Indonesia was the third position as the country with largest tobacco consumers around the world, with approximately more than 225 billion cigarettes per years, above Chine and India, or almost half the smoker of ASEAN. The Province of Bangka Belitung according to the fact become the highest smoker in Indonesia. Every day about 18,3 million cigarettes were consumed by the Bangka Belitung people, it became the highest count in Indonesia, a then the lower in Yogyakarta. This research aimed to know the effectiveness of counseling method to helping decrease smoke behavior about Poltekkes Pangkalpinang Employees. This research was used pre-experiment with one group pre-test and post-test design. All of research subject sample about 14 persons with an active smoker with variations of length since minimum about 4 years and maximum 34 years. The mean value of frequency distribution before counseling was 15,57 pc/day. Measurement after counseling decreased till 12,72 pc/day. Comparison statistic test showed that value about 0,065, then Ho un-acceptance and that mean occurring differently about smoke behavior between before and after counseling. Occurring different about smoke behavior between before and after counseling implement.